Leadership behaviour and leader self-reported well-being: A review, integration and meta-analytic examination - Kaluza, Antonia J.; Boer, Diana; Buengeler, Claudia; van Dick, Rolf (Work and stress, 2020)
While the link between leadership and follower well-being is well established, less is known about the relation between leaders' leadership behaviour and their own well-being. Particularly, a systematic integration of existing studies is missing. Based on an integrated framework summarising major theories on the leader well-being-leadership link, we quantitatively synthesised findings on the relations between different leadership behaviours and leader well-being indicators. The meta-analytical results (95 effect sizes; N = 12,617) confirmed significant relationships of constructive and destructive leadership with leader well-being in the expected directions. Relative weight analyses on the constructive leadership behaviours showed that change-oriented and relational-oriented leadership (e.g. transformational, participative) accounted for more variance in leader well-being than task-oriented leadership (e.g. transactional). Regarding destructive leadership, active destructive leadership (e.g. abusive supervision) showed stronger negative associations with leader well-being than passive leadership (e.g. laissez-faire). Based on our integrated framework, we proposed and found support for divergent patterns of associations for different forms of well-being (positive vs. negative, short-term vs. long-term, job-related vs. general). Our study demonstrates a considerable linkage between leader well-being and leadership, supporting the adoption of leadership development programmes and organisational health interventions for leaders given their impact on employees, teams and organisations.